Identifikasi dan Pengolahan Limbah Industri Susu pada Sektor Peternakan - Suryonon, Suryono (BPFP Universitas Bengkulu, 2023)
Milk is a commodity in the livestock subsector that is needed to meet the nutritional needs of the body. Demand for milk also continues to increase every year, but milk production in Indonesia has decreased in recent years, allegedly due to the Covid-19 pandemic. Therefore, the dairy industry in Indonesia continues to be developed by large companies as an effort to increase milk production and to be able to develop the domestic dairy farming sector. The dairy industry, which is run by the livestock sector, not only produces dairy products, but also produces waste in the form of solid and liquid waste. The purpose of this article is to evaluate the waste generated from the dairy industry and the potential it produces as well as ways to properly and properly manage dairy industry waste. Based on the results obtained, it shows that the dairy industry waste can be used as fertilizer and biogas from both solid waste and liquid waste from the dairy industry. Special handling of waste in the dairy processing industry is needed and can be done using traditional methods or mechanical engineering. In addition, the results of handling livestock waste also need to be tested in accordance with the standard quality standards for wastewater according to the Minister of Environment Regulation No. 5 of 2014 which aims to maintain the safety of waste water products and make them safe if they are disposed of into the environment. It can be concluded that dairy industry waste can be processed into economical products. Keywords: dairy waste, dairy industry, sewage treatment, livestock sector ABSTRAK Susu merupakan komoditas subsektor peternakan yang diperlukan untuk memenuhi kebutuhan nutrisi bagi tubuh. Permintaan susu juga terus mengalami peningkatan setiap tahunnya, namun produksi susu di Indonesia mengalami penurunan pada beberapa tahun ini diduga akibat pandemi Covid-19. Oleh sebab itu, industri susu di Indonesia terus dikembangkan oleh perusahaan besar sebagai upaya meningkatkan produksi susu serta mampu mengembangkan sektor peternakan sapi perah dalam negeri. Industri susu yang dijalankan oleh sektor peternakan tidak hanya menghasilkan produk susu, namun juga menghasilkan limbah yang berupa limbah padat dan cair. Tujuan dari artikel ini yaitu untuk mengevaluasi limbah yang dihasilkan dari industri susu dan potensi yang dihasilkan serta cara dalam pengelolaan limbah industri susu yang baik dan tepat. Berdasarkan hasil yang diperoleh menunjukkan bahwa limbah industri susu dapat dijadikan sebagai pupuk dan biogas baik dari limbah padat ataupun limbah cair dari industri susu. Penanganan khusus limbah pada industri pengolahan susu sangat diperlukan dan dapat dilakukan dengan metode tradisional ataupun dengan teknik mesin. Selain itu, hasil dari penanganan limbah ternak juga perlu diuji yang disesuaikan dengan standar baku mutu air limbah menurut Peraturan Menteri Lingkungan Hidup No. 5 Tahun 2014 yang bertujuan menjaga keamanan dari hasil air limbah dan dapat aman jika akan dibuang ke lingkungan. Dapat disimpulkan bahwa limbah industri susu dapat diolah menjadi produk yang ekonomis. Kata kunci: limbah susu, industri susu, pengolahan limbah, sektor peternakan